Anti-hnRNP B1 (RA33) Autoantibodies Are Associated with the Clinical Phenotype in Russian Patients with Rheumatoid Arthritis and Systemic Sclerosis. (4th May 2014) - Maslyanskiy, Aleksey; Lazareva, Natalya; Olinek, Polina; Schierack, Peter; Hentschel, Christian; Cuccato, Juliane; Bogdanos, Dimitrios P.; Lapin, Sergey V.; Roggenbuck, Dirk
Abstract : Heterogeneous nuclear ribonucleoproteins (hnRNPs) are potent autoantigenic targets in systemic autoimmune rheumatic diseases (SARD). Loss of tolerance to the RA33 complex consisting of hnRNP A2 and its alternatively spliced variants B1 and B2 has been the interest of rheumatologists. A novel ELISA for the detection of anti-hnRNP B1 autoantibodies has been developed to investigate the prevalence thereof in 397 patients with SARD, including patients with rheumatoid arthritis (RA), spondyloarthropathy (SPA), juvenile chronic arthritis, systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and Sjögren's syndrome (SS), in comparison to 174 controls. Anti-hnRNP B1 autoantibodies were significantly more prevalent in patients with SARD than controls (47/397, 11.8% versus 2/174, 1.1%; P < 0.001 ). In particular, anti-hnRNP B1 were found more frequently in the disease cohorts than in the controls and were present in 24/165 (14.5%) patients with RA, 6/58 (10.3%) SPA, 11/65 (16.9%) SSc, and 4/50 (8.0%) SLE. In RA patients, anti-hnRNP B1 autoantibodies correlated significantly with C-reactive protein levels and erythrocyte sedimentation rate, while in patients with SSc it was associated with features of arterial wall stiffness and presence of hypertension. Anti-hnRNP B1 autoantibodies occur in SARD and seem to be correlated with distinct clinical characteristics in patients with RA and SSc.